Evaluasi Celah Keamanan dengan Metodologi Vulnerability Assessment Sebagai Penilaian Tingkat Kerentanan pada Domain Unud.Ac.Id - Dd Hassel Putra Q; Ilham Ammarul Aziz; Eginna Gresia Br Purba; Dewa Made Wiharta; I Gusti Ayu Garnita Darmaputri (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
Website security is a crucial aspect, especially for educational institutions that manage sensitive data. Udayana University has over 500 subdomains, but not all have undergone security evaluation, potentially posing significant risks. This study aims to identify security vulnerabilities, assess risk levels, and provide mitigation recommendations. The subdomain ee.unud.ac.id was selected as a sample because it uses a template similar to many other university websites. The method employed is Vulnerability Assessment using white box testing, with tools such as OWASP ZAP, Nessus, RapidScan, and the Snort Intrusion Detection System (IDS). The analysis is based on the OWASP Top 10 (2021) and the CIA Triad principles. The results revealed 25 types of threats across three risk levels and 24 alerts from Snort, indicating potential internal and external threats. Recommended mitigations include strengthening security configurations, implementing firewalls, and regularly updating systems. This study emphasizes the importance of routine security testing and the use of IDS to safeguard systems against cyberattacks.